Pendekatan realistik dalam penaakulan dan komunikasi matematik dalam kalangan pelajar Sekolah Menengah Umum (SMU) - Herwati, Ahmad (2015)
The mathematics education curriculum in Indonesia aims for teaching and learning practices that include the use of mathematics in daily life. However, teachers give less emphasis on this aspect of usage which leads to students’ low competence in mathematical reasoning and Mathematics communication. The purpose of this study is to determine the effectiveness of the realistic approach and students’ perception towards interaction, effectiveness and responsiveness in mathematical reasoning and Mathematics communication. This study also explores mathematical reasoning and communication activities in the realistic approach. The quantitative and qualitative approach which included experiments, questionnaires and observations were used. A total of 69 year 10 students from the Riau Public Secondary School were randomly selected. Data collection was conducted twice, that is, at the pre-test and post-test stage which took eight weeks. The Mathematics test consisted of 16 items, with 12 items measuring mathematical reasoning and 4 items measuring Mathematics communication. Mathematical reasoning was measured from the analogical and generalization aspects whereas Mathematics communication was measured based on drawings, mathematical expressions and written texts. Students’ perception on interaction, effectiveness and responsiveness was measured using a questionnaire consisting of 39 items. Observations were conducted based on a check list to look at reasoning and communicative mathematical activities in the classroom. The findings show that a realistic approach can enhance analogical and generalization achievement in mathematical reasoning whereas Mathematics communication can improve achievement in drawings, mathematical expressions, and written texts. The realistic approach can improve Mathematics achievement to a higher level compared to one that does not use the realistic approach. The realistic approach also increases the level of student perception and their opportunities to explore mathematical knowledge more actively. Hence, the realistic approach has provided opportunities for students to think in a more meaningful way when solving mathematics problems and create a student-centered learning environment. Besides increasing students’ mathematics achievement, the realistic approach also improves student ability in mathematical reasoning and Mathematics communication. This study contributes to research findings in the field of mathematical reasoning and Mathematics communication in the Riau, Indonesia mathematics education curriculum.